Recommendations for the treatment of migraine attacks - a Brazilian consensus - Bordini, Carlos Alberto; Roesler, Célia; Carvalho, Deusvenir De Souza; Macedo, Djacir Dantas P.; Piovesan, Élcio; Melhado, Eliana Meire; Dach, Fabiola; Kowacs, Fernando; Silva, Hilton Mariano Da; Souza, Jano Alves De; Maciel, Jayme Antunes; Carvalho, João José De Freitas De; et al. (Academia Brasileira de Neurologia - ABNEURO, 2016)
In this article, a group of experts in headache management of the Brazilian Headache Society developed through a consensus strategic measurements to treat a migraine attack in both the child and the adult. Particular emphasis was laid on the treatment of migraine in women, including at pregnancy, lactation and perimenstrual period.

Neste artigo um grupo de especialistas no tratamento de cefaleia da Sociedade Brasileira de Cefaleia através de um consenso elaborou medidas estratérgicas para tratar uma crise de migrânea tanto na criança como no adulto. Uma enfase particular foi dada no tratamento da migranea na mulher, incluindo gravidez, lactação e período perimenstrual.
Recomendações para o tratamento da crise migranosa - Um consenso brasileiro
Keywords: headache; migraine; treatment; pain medication; crisis; cefaleia; enxaqueca; tratamento; analgésico; crise